Platinum electrolytic plating bath and platinum-plated products
By using anionic surfactant and metal salt in acidic platinum electrolytic plating bath, the problems of high stress and poor porosity of platinum film are solved, and a high-purity, dense and corrosion-resistant plating platinum products are obtained, suitable for high-demand application.
Patent Information
- Application Number
- CN202110783978.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-19
- Filing Date
- 2021-07-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-07-12
AI Technical Summary
In the existing acidic platinum electrolytic plating bath, the platinum film has problems such as high stress, poor porosity, easy pinholes and cracks, and it is difficult to obtain high-purity and dense plating products.
Add anionic surfactant with both hydrophilic and hydrophobic groups to the acidic platinum electrolytic plating bath, combine sulfuric acid or sulfamic acid, and use alkali metal element or metal salt of the second main group element to stabilize the platinum combination The precipitation of substances inhibits the formation of nitrogen oxides and sulfur oxides, and improves the density and stability of platinum particles.
It realizes the density, low porosity and high purity of platinum electrolytic precipitates, reduces the stress of platinum-plating products, improves corrosion resistance and sweat resistance, and is suitable for high-demand applications such as connectors.
Smart Images

Figure CN114752975B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an acidic platinum electrolytic plating bath and a platinum-plated product electroplated from the plating bath. Background Art
[0002] Platinum electrolytic plating baths often use divalent platinum (II) complexes as platinum compounds. Divalent platinum (II) complexes are preferably synthesized from tetravalent chloroplatinate (IV) salts as raw materials to form various platinum compounds for use. Inorganic platinum (II) complexes include compounds of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, and the like. For example, there are platinum chloride (PtCl2), platinum nitrate (Pt(NO3)2), dichlorodiammineplatinum (Pt(NH3)2Cl2, trichloroamineplatinic acid (HPtCl3(NH3)) or its salt (MPtCl3(NH3)), tetrachloroplatinic acid (H2PtCl4) or its salt (M2PtCl4), tetranitroplatinic acid (H2Pt(NO2)4) or its salt (M2Pt(NO2)4), tetrasulfoplatinic acid (H6Pt(SO3)4) or its salt (M6Pt(SO3)4), etc. Here, M represents an alkali metal element, a second main group element or ammonium. In addition, as a platinum compound, there is also a tetravalent platinum (IV) complex. The tetravalent platinum (IV) complex includes hexahydroxyplatinic acid (H2Pt(OH)6) or its salt (M'2Pt(OH)6), etc. Here, M' represents an alkali metal element, a second main group element or ammonium.
[0003] The divalent platinum (II) complexes preferably used in the electrolytic plating bath are known to include diammine dinitroplatinum (Pt(NH3)2(NO2)2, so-called p-salt), diammine dinitroplatinum dihydrate (Pt(NH3)2(H2O)2(NO2)2), diammine nitrohydroxyplatinum dihydrate (Pt(NH3)2(H2O)(OH)(NO2)), diammine nitrohydroxyplatinum (Pt(NH3)2(OH)(NO2)), diammine dinitrate platinum (Pt(NH3)2(NO3)2), dinitroplatinum sulfate (Pt(NO2)2(SO4) 2- , so-called DNS salt), tetraammineplatinum dichloride (Pt(NH3)4Cl2), diammineplatinum dichloride (Pt(NH3)2Cl2), tetraammineplatinum hydrogen phosphate (Pt(NH3)4(HPO4), so-called Q salt), etc.
[0004] Platinum electrolytic plating baths using these divalent platinum (II) complexes or tetravalent platinum (IV) complexes have been known for a long time. For example, platinum electrolytic plating baths using dinitrodiammine platinum, dinitroplatinum sulfate, etc. include the following platinum electrolytic plating baths.
[0005] For example, Japanese Patent Publication No. 36-19658 (Patent Document 1 described below) discloses an invention of an electrolyte for platinum plating comprising an aqueous solution "containing a composition obtained by heating nitrosodiammine platinum in an aqueous solution of aminosulfonic acid". The specification states that it was found that the P salt [Pt(NH3)2(NO3)2] decomposes in an aqueous solution of aminosulfonic acid, and platinum can be electroplated in the dilute solution. However, there is a disadvantage that when the platinum electrolytic plating bath is used to perform electroplating at a temperature of 70 to 80°C, the aminosulfonic acid decomposes and the platinum salt precipitates.
[0006] In addition, Japanese Patent Publication No. 36-19812 (Patent Document 2 described later) discloses an invention of a platinum-plating electrolyte comprising the following solution and water, wherein the solution is obtained by heating a composition containing 10 to 40 g of nitrosodiammine platinum per liter in about 200 cc of an aqueous mixture of 10 to 100 cc of concentrated sulfuric acid and 10 to 100 cc of concentrated phosphoric acid. However, when the platinum-plating electrolyte is used to continuously perform electroplating operations, phosphoric acid accumulates in the solution, thereby hindering the corrosion resistance of the platinum-plated film. In addition, in the platinum-plating electrolyte in which phosphoric acid is accumulated, it is difficult to reliably obtain plating of more than 5 μm with stable adhesion in a single plating operation. In addition, there is a disadvantage of hindering the recovery of platinum from the waste liquid of the platinum-plating electrolyte.
[0007] Later, the invention of "an electrolytic platinum plating bath formed by dissolving platinum diamine dinitrite in a solution containing 0.05 to 2 mol / L of a (specific) ammonium salt and 0.05 to 1 mol / L of sulfuric acid" was disclosed in Japanese Patent Publication No. 49-21018 (Patent Document 3 described below). In the examples, a bath temperature of 70 to 90°C was used. The specification states that "it has the characteristics of an industrial plating bath such as (1) high bath stability. ... (3) long bath life."
[0008] In addition, claim 4 of Japanese Patent Publication No. 08-319595 (hereinafter referred to as Patent Document 4) discloses the following invention: "A platinum bath for electroplating, wherein: in a platinum bath for electroplating containing 5 to 30 g / l of platinum as an aminosulfonate complex using a product of a reaction of 1 mol of dinitrodiammine platinum (II) with 4 to 6 mol of sulfonamide acid and having a pH value of less than 1, the electrolyte contains a maximum of 5 g / l of free sulfonamide acid and 20 to 400 g / l of a strong acid with a pH value of less than 1, and contains 0.01 to 0.2 g / l of a fluorine surfactant as a wetting agent." In the examples, the operation is performed at a bath temperature of 80°C. The specification of the invention states that "the object is to provide a platinum bath for electroplating that can deposit a smooth and shiny precipitate without cracks even if the layer thickness is greater than 100 μm and is stable even when not in use." It should be noted that "sulfonamide acid" is another name for aminosulfonic acid.
[0009] In addition, the specification of U.S. Patent No. 3206382 (Patent Document 5 described later) discloses a method for electrodepositing platinum, that is, electrolyzing an electrolyte consisting essentially of an aqueous solution of a predetermined nitroso compound complex of platinum and having a pH value of less than 2. This Example 1 discloses a method of reacting potassium tetranitroplatinate (II) with sulfuric acid to adjust potassium dinitroplatinate (II) sulfate according to the following formula.
[0010] K2Pt(NO2)4+H2SO4→K2Pt(NO2)2SO4
[0011] The specification discloses that the plating bath of the invention is stable, gives consistent results, and does not deteriorate even if left to stand.
[0012] When a platinum electrolytic plating bath is used to manufacture a platinum-plated product, a layer of nickel, copper, palladium, etc. is provided as an intermediate layer of the plated object. An acidic plating bath is usually used to form the intermediate layer, but when an acidic electrolytic plating bath is used to form the intermediate layer, an acidic plating bath is used for platinum electroplating. This is because if an alkaline platinum electrolytic plating bath is used, the acidic liquid in the previous stage will be brought into the platinum electrolytic plating bath, which easily changes the pH of the alkaline bath.
[0013] Prior art literature
[0014] Patent Literature
[0015] Patent Document 1: Japanese Patent Publication No. 36-19658
[0016] Patent Document 2: Japanese Patent Publication No. 36-19812
[0017] Patent Document 3: Japanese Patent Publication No. 49-21018
[0018] Patent Document 4: Japanese Patent Application Laid-Open No. 08-319595
[0019] Patent Document 5: U.S. Patent No. 3206382 Summary of the invention
[0020] Problems to be solved by the invention
[0021] Conventionally, platinum films electroplated from an acidic platinum electrolytic plating bath (platinum electrolytic plating solution) have problems such as high stress and easy generation of pinholes and cracks, as described in Japanese Patent Publication No. 36-19658 (the above-mentioned Patent Document 1). Although the platinum film of Japanese Patent Publication No. 08-319595 (the above-mentioned Patent Document 4) has no pinholes or cracks in appearance, when the porosity is measured, it is found that the porosity value is very poor, and pinholes and cracks still exist in the platinum film.
[0022] The problem of poor porosity of this platinum film is caused by platinum particles electrolytically precipitated by electroplating. That is, one factor is that the stable platinum complex becomes an unstable compound in the platinum electrolytic plating bath due to the extraction of platinum ions from the stable platinum complex in the platinum electrolytic plating bath. For example, when the nitro group contained in p-salts, DNS salts, etc. is coordinated to platinum, it is extremely stable, but when platinum metal is precipitated from the complex by electroplating, the remaining nitro group will form various nitrogen oxides (NOx) ions in the platinum electrolytic plating bath. The complex nitrogen oxide (NOx) ions act on the platinum complex in the platinum electrolytic plating bath, making the precipitated platinum metal particles unstable.
[0023] Specifically, tetranitroplatinic acid (H2Pt(NO2)4) may form Pt(NO2)3(H2O) in aqueous solution. - ,Pt(NO2)2(H2O)2,Pt(NO2)(H2O)3 + 、Pt(H2O)4 2+Complexes such as nitro. In addition, it is known that in aqueous solution, in addition to the above compounds, nitro groups also have the property of easily generating complex compounds of nitrogen and oxygen such as [Pt(NH3)2(NO3)2]. For example, it is known that when the nitro groups remaining in the platinum electrolytic plating bath are over-concentrated, the color tone of the platinum electrolytic plating bath will change. From this, it can also be understood that the nitro groups of the platinum complex have the property of easily generating complex compounds. In addition, it is known that in an acidic platinum electrolytic plating bath, although the sulfur oxide (SOx) ions released from the platinum complex are not as active as nitrogen oxide (NOx) ions, they also have the property of easily generating complex compounds. The electrolytic precipitate will be affected by the changes of such platinum complexes in the platinum electrolytic plating bath. In this way, there is a tendency for the electrolytic precipitate to change easily during the electroplating operation in an acidic platinum electrolytic plating bath. In particular, when continuous plating is continued under high current density conditions such as jet plating, the bath temperature rises, and new unstable compounds such as nitrogen oxide (NOx) ions and sulfur oxide (SOx) ions are easily formed.
[0024] Microscopic observation of the electrolytically precipitated platinum particles revealed that the crystal grains were large and unstable. In addition, the acidic platinum electrolytic plating bath easily dissolves metals, so platinum-plated products tend to be susceptible to the influence of metal impurities. When metal impurities accumulate and concentrate, the plating conditions of the platinum electrolytic plating bath are prone to change, which can easily lead to defects in platinum-plated products. In addition, when halide ions coexist in such a platinum electrolytic plating bath, free nitrogen oxide (NOx) ions and sulfur oxide (SOx) ions will further undergo complex reactions. The platinum ions electrolytically precipitated near the cathode are affected by various factors due to these complex compounds and ligands. Therefore, the precipitation conditions when the platinum ions become the nuclei of new platinum particles will continue to change. Since the precipitation conditions of the platinum particles on the cathode are different even if the plating conditions are the same, the platinum electrolytic precipitate will become unstable. It can be inferred that the electroplated platinum film has a high stress, large crystal grains, and pinholes and cracks.
[0025] In summary, in the previous platinum electrolytic plating bath, nitrogen oxide (NOx) ions, sulfur oxide (SOx) ions, etc. of the stable platinum complex are free, making the platinum electrolytic plating bath unstable, and these ions accumulate and concentrate. When these ions exist in a large amount in the platinum electrolytic plating bath, the conditions for the precipitation of platinum particles from the aqueous solution during electroplating become unstable. In addition, the platinum particles precipitated on the precipitated platinum particles will be affected by these ions. Therefore, the stress of the platinum precipitate precipitated by electrolysis is high, and the crystal grains grow irregularly. Therefore, the obtained platinum-plated product has the problem of more microscopic cracks and pinholes. And if copper, a metal substrate, is used for electroplating, copper is sometimes dissolved at the ppm level in an acidic platinum electrolytic plating bath. The same is true for the plating treatment of the intermediate layer of nickel, palladium, etc. Such metal impurities may have a negative impact on platinum-plated products.
[0026] However, in the previous platinum electrolytic plating bath, the influence of other metal impurities was not considered. In addition, micro cracks and pinholes in platinum-plated products have not been a problem in the past. This is because platinum-plated products have high stress and have chemical properties that are not easily corroded even if they are immersed in acid or alkali aqueous solutions. However, in the use of connectors, the porosity and corrosion resistance caused by micro cracks and pinholes in platinum-plated products become a problem. Because when the platinum-plated product is touched with bare hands, there is a risk that components such as sweat will penetrate the platinum film and corrode the metal matrix. In such uses, metal impurities at the ppm level sometimes also affect the platinum-plated product. Therefore, dense high-purity platinum-plated products and high-purity platinum electrolytic plating baths are required later. In particular, silicon exists in large quantities in nature and is a metal element that is easily involved as an impurity in platinum electrolytic plating baths. For example, precious metals are also produced as by-products of copper electrolytic refining. Referring to the twelfth embodiment of Japanese Patent Application Laid-Open No. 50-116326, it is described that a platinum-containing alloy containing silicon is produced during electrolytic refining of copper. Silicon easily enters a platinum electrolytic plating bath, so special attention is required in a high-purity platinum electrolytic plating bath.
[0027] The present invention has been made in view of the above problems, and its object is to provide a platinum electrolytic plating bath which is extremely stable and has a long bath life. In particular, it is to provide a platinum electrolytic plating bath which can obtain a high-purity platinum precipitate having a dense crystal structure similar to an amorphous state even in an acidic platinum electrolytic plating solution containing a large amount of platinum (II) complexes that are easily decomposed such as nitro groups.
[0028] Another object of the present invention is to provide a platinum-plated product having a platinum film with low stress and so dense that the grain boundaries of the platinum particles cannot be observed under a scanning electron microscope. Another object of the present invention is to provide a platinum-plated product having a high-purity platinum film that can be plated thickly. In particular, a platinum-plated product with low porosity and good corrosion resistance is provided.
[0029] Means of solving the problem
[0030] The present inventors have studied the porosity of platinum-plated products that are not easy to corrode and found that the smaller the porosity of the platinum film, the better the corrosion resistance of the platinum-plated product. It is also known that when metal impurities are present in the platinum-plated product, a dense platinum film may not be obtained due to the type and content of the metal. For example, when a conventional acidic platinum electrolytic plating bath contains specific metal impurities at the ppm level, the porosity of the electrolytically precipitated platinum precipitate may be significantly deteriorated. The platinum-plated product was observed to have surface defects such as cracks and pinholes on the platinum film.
[0031] Investigations into the sources of silicon contained in platinum electrolytic plating baths have revealed that, like the byproducts of electrolytic refining of copper mentioned above, metal impurities such as silicon are sometimes contained in the platinum matrix with a nominal concentration of 99.9% or more at tens of ppm, and silicon is also contained in distilled water. Therefore, metal impurities such as silicon may be unexpectedly accumulated when preparing platinum plating baths and replenishing evaporated water. It is also known that metal impurities such as silicon may sometimes be contained in the cleaning liquids of gold plating baths, palladium plating baths, nickel plating baths, or their recovery (Dragout) tanks, water washing devices, etc., which are pretreatment plating solutions.
[0032] The inventors first studied the platinum electrolytic plating bath under the condition of removing silicon. It was found that in the acidic platinum electrolytic plating bath with a sulfate or aminosulfonate of a divalent platinum (II) complex and free sulfuric acid or aminosulfonic acid as the base liquid, even if the platinum precipitate is of high purity, its crystal grains are large. That is, in a platinum electrolytic plating bath that does not contain metal impurities other than platinum, only platinum will be electrolytically precipitated. The electrolytically precipitated platinum is high-purity platinum, and its film characteristics can be accurately understood.
[0033] The inventors have studied various additives in such a high-purity platinum electrolytic plating bath. It was found that when an anionic surfactant having both a hydrophilic group and a hydrophobic group in one molecule was added, the platinum particles precipitated on the cathode were dense and uniform in shape. Its function is explained. That is, the anionic surfactant having both a hydrophilic group and a hydrophobic group surrounds the divalent platinum complex with one group. When power is applied to the platinum electrolytic plating bath, the anionic surfactant remains in a state of surrounding the divalent platinum complex and transports the platinum complex to the cathode surface. On the cathode surface, the divalent platinum complex becomes zero-valent platinum metal. When the divalent platinum complex contacts the cathode surface on the solution side of the cathode surface, the ligand of the platinum complex becomes nitrogen oxide (NOx) ions, etc., and is free in the platinum electrolytic plating bath. In this process, the anionic surfactant replaces nitrogen oxide (NOx) ions, etc., and surrounds the platinum metal. The free nitrogen oxide ions can no longer approach the platinum metal due to the hindrance of the anionic surfactant. When the platinum metal on the cathode is reduced to platinum particles, the platinum particles are absorbed by the platinum crystal grains, and the platinum crystal grains on the cathode grow. On the other hand, the anionic surfactant surrounding the platinum metal in the platinum electrolytic plating bath separates from the cathode surface and becomes free again in the platinum electrolytic plating bath.
[0034] use Figure 1 The role of this anionic surfactant is explained in a simple and easy-to-understand manner. Figure 1 This is a schematic diagram of a platinum electrolytic plating solution to which a p-salt of sodium lauryl sulfate is added as an anionic surfactant. For convenience, the ligand of the platinum ion is marked as sulfate ion (SO4) 2- .like Figure 1As shown on the left side of FIG. 1 , in the platinum electrolytic plating solution, sodium lauryl sulfate as an anionic surfactant surrounds the Pt(II) complex. The Pt(II) complex is transported to the cathode by external electrical energy. Figure 1 As shown in the center of the figure, the divalent Pt(II) complex transported to the cathode surface receives two electrons from the cathode and is reduced to zero-valent Pt(0) metal, which is surrounded by anionic surfactants. On the plating solution side on the cathode, the anionic surfactants of the zero-valent Pt(0) metal and the anionic surfactants of the Pt(II) complex repel each other. In addition, they also repel hydroxide ions (not shown) and sulfur oxide (SOx) ions (not shown) generated by electrolysis. Therefore, the interaction between the zero-valent Pt(0) metal and the platinum atoms in the divalent Pt(II) complex is suppressed.
[0035] Next, if Figure 1 As shown on the right side of the figure, the zero-valent Pt(0) metal is reduced to platinum particles (not shown) and absorbed by the platinum crystal grains. On the cathode, the platinum crystal grains grow to form a platinum-plated film. On the other hand, the anionic surfactant surrounding the platinum metal separates from the cathode and becomes free again in the platinum electrolytic plating solution. Through the action of such anionic surfactants, the platinum particles can suppress the interaction of other platinum atoms, so that the platinum particles can always be precipitated under constant conditions. When the homogenized crystalline particles are stacked on the cathode surface, a seamless electrolytic precipitate is formed. As a result, a dense platinum film with a crystal structure similar to that of an amorphous state is obtained on the cathode.
[0036] On the other hand, it is known that such anionic surfactants are ineffective against metal impurities in platinum electrolytic plating baths. The action of anionic surfactants is effective against the ligands of platinum complexes, but is ineffective against metal impurities in platinum electrolytic plating solutions. When the platinum electrolytic plating bath of the present invention contains metal impurities such as silicon, these metal impurities coprecipitate in the platinum-plated film. On the contrary, if the platinum electrolytic plating bath does not contain these metal impurities, a high-purity platinum electrolytic precipitate can be obtained. It is known that a high-purity platinum-plated film that does not contain metal impurities is an electrolytic precipitate that has a low tensile stress, is dense, and has a low porosity even if it has a high hardness.
[0037] Scanning electron microscope images of the surface and cross section of the platinum electrolytic precipitate of the present invention are shown in Figure 2 The figure is a photograph of the surface of a platinum electrolytic precipitate with a purity of 99% or more (the upper part of the photo divided by a white horizontal line) and a cross section with a thickness of 4 μm (the lower part of the photo) taken from above at a 45-degree angle. As can be seen from the figure, the crystal grains of the platinum electrolytic precipitate are dense like an amorphous state.
[0038] The platinum electrolytic plating bath of the present invention that can solve the above-mentioned problems is gist of an acidic platinum plating bath containing a divalent platinum (II) complex and free sulfuric acid or aminosulfonic acid and containing an anionic surfactant.
[0039] In addition, the platinum electrolytic plating bath of the present invention that can solve the above-mentioned problems is mainly composed of an anionic surfactant and a metal salt of a second main group element or a metal salt of an alkali metal element in an acidic platinum plating bath containing a divalent platinum (II) complex and free sulfuric acid or aminosulfonic acid. Here, the second main group element refers to elements such as beryllium, magnesium, calcium, and strontium. In addition, the alkali metal element refers to elements such as lithium, sodium, potassium, and rubidium.
[0040] The platinum electrolytic precipitate of the platinum electrolytic plating bath of the present invention that can solve the above-mentioned problems mainly has a platinum purity of 99% by weight or more, a Vickers hardness of 450 to 500 Hv, a stress of 100 MPa or less, and a porosity of 30% or less.
[0041] Effects of the Invention
[0042] The platinum electrolytic plating bath of the present invention contains an anionic surfactant, so that even if it is an acidic platinum plating bath, it has a crystal structure like an amorphous state, and has the effect of obtaining a dense platinum electrolytic precipitate. That is, the platinum electrolytic precipitate of the present invention has the following characteristics: it is glossy, and even if it is hard and dense, the stress is extremely low. In particular, the high-purity platinum electrolytic plating bath that does not contain metal impurities such as silicon will increase the above effect.
[0043] The platinum electrolytic plating bath of the present invention has the effect of reducing the amount of anionic surfactant used by containing alkali metal elements, second main group elements or metal salts of these metal elements. That is, it is known that by containing alkali metal elements, second main group elements or metal salts of these metal elements in addition to anionic surfactants, the same effect can be obtained even if the content of anionic surfactants is small. In addition, the platinum electrolytic plating bath of the present invention also has the effect of less accumulation of anionic surfactants even if electroplating is carried out continuously for a long time. It also has the effect that the platinum electrolytic plating bath of the present invention can be operated continuously for a long time even if the anionic surfactant sometimes deteriorates and the surfactant concentration is substantially reduced.
[0044] In addition, the platinum electrolytic plating bath of the present invention can provide a plating film with low porosity and excellent corrosion resistance even if the plating film is thin and equal to or less than 1 μm, which is dense and has a crystal structure similar to that of an amorphous state. Furthermore, if a high-purity platinum electrolytic plating bath is used, the purity of the platinum electrolytic precipitate is high and the quality of the platinum film is stable.
[0045] In addition, the platinum electrolytic plating bath of the present invention has a stable plating quality, so the bath temperature can be set to a relatively low temperature. When the bath temperature of the platinum electrolytic plating bath of the present invention is lowered, the management of the plating solution becomes easier. In addition, the accumulation of impurities in the platinum electrolytic plating bath of the present invention is small, so there is no need to set up expensive equipment such as filtering and separating the plating solution.
[0046] The platinum film of the platinum-plated product of the platinum electrolytic precipitate of the platinum electrolytic plating bath of the present invention has dense crystal grains and a crystal structure like an amorphous state. Such a platinum film has a low porosity and therefore has excellent corrosion resistance. In particular, it has the effect of being able to obtain a platinum-plated product with high corrosion resistance even if it is a thin plating of less than or equal to 1 μm. The corrosion resistance of the platinum-plated product of the present invention includes not only static corrosion resistance such as against corrosive liquid, but also dynamic corrosion resistance when weak current is flowing. In addition, the platinum-plated product of the present invention is hard and dense, so when used as a connector, it has the effects of excellent plug-in durability and wear resistance. The stress of the platinum film of the present invention is extremely low, so it also has the effects of strong adhesion, no peeling of the film, and no pinholes or cracks on the film.
[0047] In addition, the high-purity platinum-plated product of the present invention has the effect of stabilizing the temperature coefficient of resistance and obtaining a uniform resistance value. In addition, the platinum-plated product of the present invention is a platinum electrolytic precipitate that is glossy and corrosion-resistant even at high purity, and thus has the effect of being suitable as a decorative item. In particular, the porosity shows a corrosion resistance standard that is more stringent than sweat resistance, and has the effect of being suitable for use as jewelry such as bracelets and earrings. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is an explanatory diagram for explaining the principle of the platinum plating bath of the present invention.
[0049] Figure 2 This is a scanning electron microscope photograph of the platinum electrolytic precipitate of the present invention. DETAILED DESCRIPTION
[0050] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0051] Hereinafter, embodiments of the platinum electrolytic plating bath of the present invention and a platinum-plated product including a platinum electrolytic precipitate produced using the platinum electrolytic plating bath will be described.
[0052] <Platinum electrolytic plating bath>
[0053] Platinum(II) complex
[0054] In the platinum electrolytic plating bath of the present invention, the divalent platinum (II) complex can use the divalent platinum (II) complex preferably used in the conventional electrolytic plating bath. The divalent platinum (II) complex is preferably an inorganic platinum complex having at least one ligand selected from nitro (NO2), nitrate (NO3), sulfate (SO4) or sulfone (SO3) and amino (NH3), oxonium (H2O) or hydroxyl (OH). The divalent platinum (II) complex particularly preferably used in the electrolytic plating bath includes p salts, DNS salts, etc. These platinum (II) complexes can be used alone or in combination of two or more.
[0055] In the platinum electrolytic plating bath of the present invention, an aqueous solution of a divalent platinum (II) complex dissolved in free sulfuric acid or aminosulfonic acid is used. For example, if a divalent platinum complex powder such as p salt, DNS salt, etc. is dissolved in a sulfuric acid solution or an aminosulfonic acid solution, a brown or light yellow liquid is obtained. The platinum electrolytic plating bath of the present invention can directly use the divalent platinum solution or can dilute the divalent platinum solution for use. In the platinum electrolytic plating bath of the present invention, the so-called "sulfuric acid or aminosulfonic acid" means that sulfuric acid or aminosulfonic acid can be used alone or mixed.
[0056] The concentration of platinum (the total content when two or more platinum salts are used) as the platinum (Pt) content is preferably 1 to 20 g / L, and more preferably 2.5 to 15 g / L. If the concentration of platinum is less than 1 g / L, there is a situation where the precipitation rate slows down, but when there is a metal salt, the delay in the precipitation rate is alleviated. In addition, when visually observed, if the concentration of platinum is less than 1 g / L, sometimes precipitation abnormalities such as overburned plating and unevenness are found in the plated film. On the other hand, even if the concentration of platinum is greater than 20 g / L, the effect of platinum electroplating will hardly change. Therefore, when the concentration of platinum (II) ions is greater than 20 g / L, the substrate cost increases. If the concentration of platinum is in the range of 2.5 to 15 g / L, continuous plating can be stably implemented. It should be noted that the amount of phosphoric acid contained in platinum complexes such as Q salts can be appropriately adjusted by using them in combination with other platinum complexes that do not contain phosphorus.
[0057] The content of free sulfuric acid or aminosulfonic acid in the platinum electrolytic plating bath of the present invention is preferably 30 to 600 g / L, and more preferably 50 to 400 g / L, whether used alone or in combination of two or more. If the total content of free sulfuric acid or aminosulfonic acid is less than 30 g / L, although it also depends on the content of other auxiliary conductive salts, precipitation abnormalities such as overburned plating and unevenness may sometimes be found on the plated film. On the other hand, when the total content of free sulfuric acid or aminosulfonic acid is greater than 600 g / L, there is a risk that the concentration of free sulfate becomes too high and the balance of the platinum electrolytic plating solution is lost due to the evaporation loss of water in the plating operation.
[0058] Anionic surfactants
[0059] The platinum electrolytic plating bath of the present invention contains anionic surfactants. As the anionic surfactant in the platinum electrolytic plating bath of the present invention, generally known anionic surfactants such as sulfonic acid type, sulfate type, fatty acid type, etc. can be used. However, phosphate type surfactants are not preferred as anionic surfactants of the present invention because the phosphate salt as a component sometimes hinders the corrosion resistance of the platinum electrolytic precipitate. Specifically, the following anionic surfactants can be cited, but they are not limited to these. As long as they are products sold as anionic surfactants, they can be used without problems except for phosphate type anionic surfactants.
[0060] Sulfonic acid type anionic surfactants include alkyl sulfonates such as sodium undecylsulfonate and sodium octadecylsulfonate, alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate, and sulfosuccinates such as sodium dialkylsulfosuccinate.
[0061] Sulfate ester type anionic surfactants include sodium lauryl sulfate, ammonium lauryl sulfate, etc.
[0062] Fatty acid type anionic surfactants include sodium laurate, sodium stearate, etc., as well as amino acid substances such as sodium N-decanoyl sarcosinate, N-lauroyl-N-methyl-β-alanine and other amino acids such as sodium decanoyl sarcosinate.
[0063] The above-mentioned anionic surfactant is preferably an alkali metal salt of alkylated sulfuric acid or its salt and alkylbenzenesulfonic acid or its salt, stearic acid or its salt, sulfonic acid or its salt or lauryl sulfate, a salt of a second main group element, an ammonium salt, etc. Because these anionic surfactants will be incorporated into the sulfate or aminosulfonate of the divalent platinum (II) complex, the electrolytic precipitate will be dense. A small amount of anionic surfactant will act on the platinum electrolytic precipitate and has the property of converting the crystal grains into an amorphous state. In addition, the anionic surfactant is not easy to evaporate from the platinum electrolytic plating bath, so it acts on the platinum electrolytic precipitate stably for a long period of time in the platinum electrolytic plating bath. The anionic surfactant is not limited to the use of one type, and two or more types can be used in combination. Because the platinum electrolytic plating bath is sometimes circulated by a pump, it is preferred to use a non-foaming anionic surfactant.
[0064] The small amount of anionic surfactant in the platinum electrolytic plating bath of the present invention is preferably in the range of 5 to 500 mg / L. If the content of anionic surfactant is less than 5 mg / L, the stress of the platinum electrolytic precipitate increases, and most of them cannot play the effect of improving corrosion resistance. The lower limit of the total amount of anionic surfactant is preferably 20 mg / L, and more preferably 50 mg / L. When containing salts of alkali metal elements or second main group elements, the content of anionic surfactant 50 mg / L can be relatively reduced to less than 15 mg / L. When containing salts of alkali metal elements or second main group elements, the content of anionic surfactant 5 mg / L can be relatively reduced to less than 3 mg / L. On the other hand, when the content of anionic surfactant is more than 500 mg / L, precipitation abnormalities such as overburned plating and unevenness are often found on the plating film during visual observation. In addition, the upper limit is preferably 300 mg / L, and more preferably 200 mg / L. When containing salts of alkali metal elements or second main group elements, the content of anionic surfactant can also be relatively reduced.
[0065] Metal Salts
[0066] It is known that in the platinum electrolytic plating bath of the present invention, when there is a metal salt of a second main group element or a metal salt of an alkali metal element, the content of anionic surfactant can be reduced. In the platinum electrolytic plating bath of the present invention, the metal salt of the second main group element or the metal salt of an alkali metal element has a large ionization tendency, so even if the electroplating operation is performed, these metals will not coprecipitate into the platinum electrolytic precipitate. In addition, these metal salts do not have the effect of hindering the growth of platinum particles like anionic surfactants. Among the metal salts of the second main group element or the metal salts of the alkali metal element, magnesium salts are particularly preferred. As magnesium salts, there are, for example, magnesium sulfate, magnesium sulfite, magnesium nitrate, and their water and products. Magnesium acetate, magnesium citrate, magnesium lactate, magnesium stearate, etc. can also be used. In addition, substances that form salts in the platinum electrolytic plating bath of the present invention, such as magnesium oxide and magnesium hydroxide, can also be used as raw materials. The platinum electrolytic plating bath of the present invention contains free sulfuric acid or aminosulfonic acid, so it is better to use cheap metal sulfates as metal salts of the second main group element or metal salts of alkali metal elements.
[0067] If there are metal impurities such as silicon other than metal salts of the second main group elements and metal salts of alkali metal elements in the platinum electrolytic plating bath, these impurity metals are easily precipitated into the platinum electrolytic precipitate. If these metal impurities are precipitated into the platinum electrolytic precipitate, although it also depends on the type and content of these metal impurities, it sometimes has a negative impact on the porosity of the platinum film, that is, the corrosion resistance of the platinum-plated product. Therefore, in the case of obtaining a high-purity platinum electrolytic precipitate, it is necessary to remove these impurity metals as much as possible. In particular, silicon is an impurity element that easily enters the platinum electrolytic plating bath of the present invention. In the case of obtaining a high-purity platinum electrolytic precipitate, silicon can be used as an indicator of impurities. Silicon is preferably less than or equal to 1ppm. In addition, the metal salt of the second main group element or the metal salt of the alkali metal element does not contain halogen elements. Because halogen elements will have a negative impact on the platinum electrolytic precipitate. These metal salts also do not contain phosphates. Because a platinum electrolytic plating bath containing a large amount of phosphate will deteriorate the corrosion resistance of the platinum electrolytic precipitate. Although phosphorus has the effect of making the platinum precipitate dense, phosphate has the property of not being easy to evaporate. If phosphate is used as the metal salt of the second main group element or the metal salt of the alkali metal element, it will be concentrated, so that phosphorus is contained in the platinum electrolytic precipitate, and there is a risk of negatively affecting the platinum-plated product.
[0068] Other additives
[0069] The platinum electrolytic plating bath of the present invention can use known additives such as pH buffers. As a pH buffer, there is no particular limitation as long as it is a known pH buffer. As preferred buffers, inorganic salts such as potassium hydroxide, sodium hydroxide, magnesium hydroxide, calcium hydroxide, or acetic acid, boric acid, tetraboric acid, citric acid, malic acid, succinic acid, malonic acid, maleic acid, fumaric acid, glycine or their compounds (potassium salt, sodium salt, ammonium salt, etc.) can be cited. These pH buffers can be added in a concentration range of 0.1 to 100 g / L. And the platinum electrolytic plating bath of the present invention can also contain functional additives such as ligands, bath stabilizers, speed adjusters, levelers, crystal adjusters, stress relaxers, and physical property enhancers as needed. However, functional additives that cannot maintain a high purity of 99% or more of the platinum electrolytic precipitate and functional additives that deteriorate the porosity are excluded.
[0070] Plating conditions, etc.
[0071] In the platinum electrolytic plating bath of the present invention, the pH is preferably less than or equal to 2, and more preferably less than or equal to 1.5. This is because an anionic surfactant is contained. Also, during the electroplating operation, the sulfate or aminosulfonate of the divalent platinum (II) complex is stable. The pH is usually in the range of 0.2 to 1.0. In order to control the pH within a specified range, a pH buffer can be used. The pH buffer can be used alone or in combination of two or more. In addition, the bath temperature can be appropriately determined according to the surrounding environment of the plating operation. It is preferably in the range of 30 to 90°C, more preferably in the range of 35 to 70°C, and even more preferably in the range of 40 to 60°C. The higher the bath temperature, the faster the precipitation rate of the platinum electrolytic precipitate, but the more the evaporation of the plating solution. The bath temperature can be appropriately determined according to the metal substrate used and the purpose of the platinum product. In addition, the application range of the cathode current density is large, and the optimal current density can be selected in combination with the plating area of the metal substrate, the selection of immersion and spray plating equipment, the flow rate of the plating solution and other conditions.
[0072] <Platinum electrolytic precipitate>
[0073] The object to be plated in the platinum electrolytic plating bath of the present invention is used as a metal substrate. The metal substrate can be any material that can be electroplated on its surface, and there is no limitation even if the substrate is an insulating material such as plastic or ceramic. The surface of the metal substrate is appropriately selected from metals or alloys according to the intended use. In the use of electrical and electronic components such as connectors, in addition to copper metal and copper alloys, metals such as iron, nickel, chromium, and their alloys are usually used. In addition, the surface of the metal substrate can also be electrolessly plated or electroplated with nickel, palladium, gold, etc. In addition, for electrode use, refractory metals such as titanium and tantalum are used. For jewelry and decorative uses, metals such as stainless steel, nickel, silver alloys, and gold alloys are used. In addition, thickly plated platinum electrolytic precipitates can also be used for decorative items and ornaments.
[0074] The platinum electrolytic precipitate of the present invention is dense, and no cracks or pinholes are seen. The platinum electrolytic precipitate of the present invention is subjected to a porosity test, which is a corrosion resistance test as shown in the examples. This is because even if an artificial sweat test (JIS B 7285) or an accelerated corrosion test (JIS H 8502) is performed, it is difficult to evaluate the difference in corrosion. In addition, the internal stress of the platinum electrolytic precipitate of the present invention is low, and thick plating with a thickness of 10 μm or more can be performed. In addition, even if the platinum film is peeled off from the metal substrate, no bending or curling is seen in the platinum film of the present invention.
[0075] In the platinum-plated product of the present invention, a double-layer structure of a metal substrate and a platinum electrolytic precipitate is preferred. In this way, the cost required for the expensive platinum substrate can be saved. As mentioned above, the metal substrate is appropriately selected according to the purpose. The metal substrate can be either a single metal or a laminated metal. Single metals and laminated metals also include metals coated on plastics, ceramics, etc. In addition, the platinum-plated product of the thin plated film of the present invention is more preferably a connector. The platinum electrolytic precipitate of the present invention is a crystalline structure like an amorphous state, with low porosity, high hardness, and corrosion resistance. Therefore, even if the surface of the thinner platinum electrolytic precipitate is touched with bare hands, it will not corrode. It should be noted that although the porosity also depends on the film thickness of the plated film, it is preferably less than or equal to 25%, and more preferably less than or equal to 20%.
[0076] Example
[0077] Hereinafter, the present invention will be specifically described using Examples and Comparative Examples, but the present invention is not limited to these Examples unless it exceeds the gist of the present invention.
[0078] Example
[0079] Example 1
[0080] The platinum stock solution of Example 1 is a sulfuric acid solution containing DNS, and the DNS contains 11 g / L in terms of platinum. Sulfuric acid and aminosulfonic acid are added in equal amounts to the platinum stock solution, and a total of 160 g / L is added to prepare a basic bath. 60 mg / L of sodium lauryl sulfate ("Emal (registered trademark of the company) 0" manufactured by Kao Corporation) is added to the basic bath as an anionic surfactant, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0081] Example 2
[0082] The platinum stock solution of Example 2 is an aminosulfonic acid solution containing 15 g / L of p-salt in terms of platinum. 70 g / L of sulfuric acid is added to the platinum stock solution to prepare a basic bath. 70 mg / L of sodium dodecylbenzenesulfonate ("Neopelex (registered trademark of the company) G-15" manufactured by Kao Corporation) is added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0083] Example 3
[0084] The platinum stock solution of Example 3 is an aminosulfonic acid solution containing 17 g / L of DNS in terms of platinum. Sulfuric acid and aminosulfonic acid are added in equal amounts to the platinum stock solution, and a total of 150 g / L is added to prepare a basic bath. 180 mg / L of N-lauroylsarcosine sodium salt (purity greater than or equal to 95.5%) is added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0085] Example 4
[0086] The platinum stock solution of Example 4 is a mixed solution of sulfuric acid and aminosulfonic acid containing 16 g / L of DNS in terms of platinum. 60 g / L of aminosulfonic acid is added to the platinum stock solution to prepare a basic bath. 400 mg / L of alkyl allyl sulfonate and alkyl ammonium salt ("VISCO TOP (registered trademark of the company) 200LS-2" manufactured by Kao Corporation) is added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0087] Example 5
[0088] The platinum stock solution of Example 5 is a mixed solution of sulfuric acid and aminosulfonic acid containing 5 g / L of DNS in terms of platinum. 80 g / L of sulfuric acid is added to the platinum stock solution to prepare a basic bath. 500 mg / L of ammonium lauryl sulfate ("Emal (registered trademark of the company) AD-25R" manufactured by Kao Corporation) is added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0089] Example 6
[0090] The platinum stock solution of Example 6 is an aminosulfonic acid solution containing 3 g / L of DNS in terms of platinum. 180 g / L of aminosulfonic acid is added to the platinum stock solution to prepare a basic bath. 90 mg / L of sodium stearate is added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0091] Example 7
[0092] The platinum stock solution of Example 7 is a sulfuric acid solution containing 13 g / L of p-salt in terms of platinum. 110 g / L of aminosulfonic acid is added to the platinum stock solution to prepare a basic bath. 160 mg / L of linear sodium alkylbenzene sulfonate ("Newrex (registered trademark of the company) Soft Type 30" manufactured by NOF Corporation) is added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0093] Example 8
[0094] The platinum stock solution of Example 8 is a mixed solution of sulfuric acid and aminosulfonic acid containing 1 g / L of DNS in terms of platinum. Sulfuric acid and aminosulfonic acid are added in equal amounts to the platinum stock solution, and a total of 80 g / L is added to prepare a basic bath. 10 mg / L of ammonium lauryl sulfate ("Emal (registered trademark of the company) AD-25R" manufactured by Kao Corporation) and 15 g / L of magnesium sulfate are added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0095] Example 9
[0096] The platinum stock solution of Example 9 is an aminosulfonic acid solution containing 18 g / L of p-salt in terms of platinum. 190 g / L of aminosulfonic acid is added to the platinum stock solution to prepare a basic bath. 140 mg / L of potassium lauryl sulfate manufactured by Tokyo Chemical Industry Co., Ltd. and 6 g / L of magnesium sulfate are added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0097] Example 10
[0098] The platinum stock solution of Example 10 is a sulfuric acid solution containing 8 g / L of DNS in terms of platinum. 130 g / L of sulfuric acid is added to the platinum stock solution to prepare a basic bath. 200 mg / L of linear alkylbenzene sulfonate sodium ("Neogen (registered trademark of the company) AS-20" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 2 g / L of magnesium sulfate are added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0099] Embodiment 11
[0100] The platinum stock solution of Example 11 is a mixed solution of sulfuric acid and aminosulfonic acid containing 14 g / L of p-salt in terms of platinum. 200 g / L of sulfuric acid is added to the platinum stock solution to prepare a basic bath. 300 mg / L of sodium stearate and 4 g / L of calcium sulfate are added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0101] Example 12
[0102] The platinum stock solution of Example 12 is a mixed solution of sulfuric acid and aminosulfonic acid containing 6 g / L of DNS in terms of platinum. Sulfuric acid and aminosulfonic acid are added in equal amounts to the platinum stock solution, and a total of 140 g / L is added to prepare a basic bath. 80 mg / L of "sodium 1-octadecylsulfonate" manufactured by Tokyo Chemical Industry Co., Ltd. and 20 g / L of magnesium sulfate are added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0103] Example 13
[0104] The platinum stock solution of Example 13 is an aminosulfonic acid solution containing 7 g / L of DNS in terms of platinum. 120 g / L of sulfuric acid is added to the platinum stock solution to prepare a basic bath. 5 mg / L of "sodium dimethyl isophthalate-5-sulfonate" manufactured by Tokyo Chemical Industry Co., Ltd. and 1 g / L of sodium sulfate are added to the basic bath, and the pH is adjusted to 0.4 to prepare a platinum electrolytic plating bath.
[0105] The platinum electrolytic plating baths of Examples 1 to 13 are prepared by dissolving p-salt or DNS in sulfuric acid or aminosulfonic acid to prepare a platinum concentrate containing a divalent platinum complex. Then, sulfuric acid, aminosulfonic acid or a mixture thereof is added to the platinum concentrate to prepare a platinum base bath. A predetermined surfactant is then added to the base bath to prepare the platinum electrolytic plating baths of Examples 1 to 13. In addition, sulfate is added as a metal salt to the platinum electrolytic plating baths of Examples 8 to 13.
[0106] The components of the platinum electrolytic plating baths of Examples 1 to 13 are selected and shown in Table 1. It should be noted that the pure water used for dilution is deionized water treated by an ion exchange resin device. In any of the platinum electrolytic plating baths of Examples 1 to 13, silicon as an impurity is less than or equal to 0.1 ppm.
[0107] Table 1
[0108]
[0109] All the metal substrates to be plated were made of the same copper specimen (a specimen with a conductor welded on a 20 mm × 40 mm × 0.1 mm thick sheet). The specimen was pre-treated by degreasing and pickling. Then, the platinum electrolytic plating bath of Examples 1 to 13 was used to pass a cathode current density of 2 A / dm at a bath temperature of 55°C through the pre-treated specimen. 2 Platinum was electroplated directly on the test piece from each platinum electrolytic plating bath using a current of 0.32 A.
[0110] Thus, platinum electrolytic precipitates of 0.8 μm were precipitated from the platinum electrolytic plating baths of Examples 1 to 13 to form platinum films of Examples 01 to 13. The platinum purity of the platinum films of Examples 01 to 13 was 99%, and all of these platinum films were glossy. The porosity, hardness, and internal stress of the platinum films of Examples 01 to 13 were then measured. The results are shown in Table 2.
[0111] Table 2
[0112]
[0113] Here, the porosity test is a test adopted because platinum electrolytic precipitates do not corrode in ordinary corrosion tests. The porosity test is to apply a low voltage of 0.74V to a 5% sulfuric acid electrolyte at 50°C, use the platinum film of the implemented product as the anode, and electrolyze for 20 minutes. On the platinum film after electrolysis, the copper surface is exposed. The exposed copper is measured by the current value of the rectifier, and the proportion of copper exposed on the surface of the platinum film is inferred based on the numerical change of the current value, which is defined as "porosity". That is, a porosity of 100% is the current value when copper is exposed on the surface of the platinum film on the entire surface, and a porosity of 0% is the current value when copper is not exposed at all. The porosity of the platinum film of implemented products 01 to 13 is a percentage distributed according to the current value ratio of porosity 100% and porosity 0%. The smaller the value of the porosity, the more corrosion-resistant it is.
[0114] As shown in the above test results, the platinum films of the embodiments 01 to 13 of the present invention are glossy even if the film thickness is as thin as 0.8 μm. It can also be seen that the Vickers hardness of these platinum films is 450 to 480 Hv, which is relatively hard, and the porosity is also in the range of 8.5 to 13.5%, which is excellent in corrosion resistance. In addition, the purity of platinum in these platinum films is 99%. It can also be seen that the internal stress of these platinum films is in the range of 20 to 80 MPa, which is extremely low.
[0115] On the other hand, no correlation was found between the porosity and stress of the platinum films of the embodiments 01 to 13 of the present invention. Therefore, an attempt was made to compare the embodiments 09 and 10 with the embodiments 05 and 07 individually. The platinum electrolytic plating bath of the embodiment 09 contained 140 mg / L of potassium lauryl sulfate and 6 g / L of magnesium sulfate. On the other hand, the platinum electrolytic plating bath of the embodiment 05 contained 500 mg / L of ammonium lauryl sulfate and did not contain magnesium sulfate. The platinum electrolytic plating bath of the embodiment 10 contained 200 mg / L of sodium alkylbenzene sulfonate and 2 g / L of magnesium sulfate. On the other hand, the platinum electrolytic plating bath of the embodiment 07 contained 160 mg / L of sodium alkylbenzene sulfonate and did not contain magnesium sulfate.
[0116] Comparing the porosity of the platinum film, the porosity of the embodiment 09 is 9.5%, while the porosity of the embodiment 05 is 11.4%. In addition, the porosity of the embodiment 10 is 11%, while the porosity of the embodiment 07 is 12.5%. That is, it can be seen that the platinum films of the embodiment 09 and the embodiment 10 containing metal sulfates have lower porosity and higher corrosion resistance than the platinum films of the embodiment 05 and the embodiment 07 not containing metal sulfates, regardless of the type of platinum compound. In addition, comparing the stress of the platinum film, the stress of the embodiment 09 is 20MPa, while the stress of the embodiment 05 is 60MPa. In addition, the stress of the embodiment 10 is 20MPa, while the stress of the embodiment 07 is 50MPa. That is, it can be seen that the stress of the platinum films of the embodiment 09 and the embodiment 10 containing metal sulfates has lower internal stress than the platinum films of the embodiment 05 and the embodiment 07 not containing metal sulfates, regardless of the type of platinum compound. It should be noted that the hardness of the platinum film of Example 05, Example 07, Example 09, and Example 10 is 450 Hv or more.
[0117] Figure 2 The scanning electron microscope photograph of the platinum electrolytic precipitate of 4 μm from the platinum electrolytic plating bath of Example 1 is shown. Figure 2 As shown in the photographs, there is no difference in the size of the crystal grains of the platinum electrolytic precipitate on the surface and in the cross-section, and the platinum film is so dense that the grain boundaries of the platinum particles cannot be observed using a scanning electron microscope. When the platinum film was subjected to X-ray diffraction, the crystal orientation of the platinum was observed. In this specification, the precipitation form of such a platinum electrolytic precipitate is referred to as "amorphous crystal structure". It can be seen that the particles of the platinum electrolytic precipitate of Example 1 have an amorphous crystal structure and are very small and dense. Therefore, the plated product of the present invention has excellent corrosion resistance such as sweat resistance. It should be noted that even when the platinum electrolytic precipitate is precipitated to a size of 10 μm or more from the platinum electrolytic plating bath of Example 1, the platinum film maintains an amorphous crystal structure.
[0118] Embodiment 14
[0119] The platinum stock solution of Example 14 is an aminosulfonic acid solution containing 4 g / L of Q salt in terms of platinum. 70 g / L of sulfuric acid is added to the platinum stock solution to prepare a basic bath. 250 mg / L of N-lauroyl-N-methyl-β-alanine ("ALANON ALA" manufactured by Kawaken Fine Chemicals Co., Ltd.) as an anionic surfactant is added to the basic bath, and 5 g / L of magnesium sulfate is added to adjust the pH to 0.5 to prepare a platinum electrolytic plating bath.
[0120] Embodiment 15
[0121] The platinum stock solution of Example 15 is an aminosulfonic acid solution containing 8 g / L of Q salt in terms of platinum. 70 g / L of aminosulfonic acid is added to the platinum stock solution to prepare a basic bath. 250 mg / L of a polycarboxylate ("CARRYBON L-400" manufactured by Sanyo Chemical Industries, Ltd.) as an anionic surfactant is added to the basic bath, and the pH is adjusted to 1.5 to prepare a platinum electrolytic plating bath.
[0122] Example 16
[0123] The platinum stock solution of Example 16 is an aminosulfonic acid solution containing 10 g / L of Q salt in terms of platinum. 50 g / L of aminosulfonic acid is added to the platinum stock solution to prepare a basic bath. 100 mg / L of sodium dialkyl sulfosuccinate (manufactured by Kao Corporation, PELEX OT-P) as an anionic surfactant is added to the basic bath, and the pH is adjusted to 1.5 to prepare a platinum electrolytic plating bath.
[0124] The components of the platinum electrolytic plating baths of Examples 14 to 16 are extracted and shown in Table 3. In any platinum electrolytic plating bath, silicon as an impurity was 0.1 ppm or less.
[0125] Table 3
[0126]
[0127] As in Example 1, the same copper test piece (a test piece in which a wire is welded on a sheet of 20 mm×40 mm×0.1 mm thick) was used to precipitate a platinum electrolytic precipitate of 0.8 μm at the same cathode current density. The platinum purity of the platinum electrolytic precipitates of Examples 14 to 16 was 99%, and these platinum electrolytic precipitates were all glossy. The porosity of the platinum electrolytic precipitates of Examples 14 to 16 was measured, and the hardness and internal stress were measured.
[0128] The porosity, hardness and internal stress of the embodiment 14 were 11.5%, 470 Hv and 40 MPa. In addition, the porosity, hardness and internal stress of the embodiment 15 were 13.8%, 465 Hv and 80 MPa. In addition, the porosity, hardness and internal stress of the embodiment 16 were 10.2%, 480 Hv and 20 MPa. The results are shown in Table 4.
[0129] Table 4
[0130]
[0131] Comparative Example
[0132] Comparative Example 1
[0133] Comparative Example 1 is the same as Example 1 except that it does not contain anionic surfactant, and contains 11 g / L of DNS in terms of platinum, and is a platinum electrolytic plating bath to which sulfuric acid and aminosulfonic acid are added in equal amounts to add a total of 160 g / L.
[0134] Comparative Example 2
[0135] Comparative Example 2 is a platinum electrolytic plating bath to which 5 g / L of tetraammine platinum (II) hydrogen phosphate (5 g / L in terms of platinum) and disodium hydrogen phosphate dihydrate were added and adjusted to pH 10.5 using a sodium hydroxide solution.
[0136] Comparative Example 3
[0137] Comparative Example 3 is a platinum electrolytic plating bath similar to that of Example 1 except that 600 mg / L of sodium lauryl sulfate ("Emal (registered trademark) 0" manufactured by Kao Corporation) was added.
[0138] As in Example 1, the same copper test piece (a test piece in which a conductor is welded on a sheet of 20 mm×40 mm×0.1 mm thick) was used to precipitate a platinum electrolytic precipitate of 0.8 μm. The platinum purity of the platinum electrolytic precipitates of Comparative Products 01 to 03 was 99%, and all of these platinum electrolytic precipitates were glossy. In addition, the porosity of the platinum electrolytic precipitates of Comparative Products 01 to 03 was measured, and the hardness and internal stress were measured.
[0139] The porosity, hardness and internal stress of comparative product 01 are 30.6%, 400 Hv and 450 MPa. In addition, the porosity, hardness and internal stress of comparative product 02 are 35.1%, 420 Hv and 550 MPa. In addition, the porosity, hardness and internal stress of comparative product 03 are 33.5%, 410 Hv and 510 MPa. The results are shown in Table 3.
[0140] As shown in the above test results, the platinum electrolytic precipitates of the embodiments 14 to 16 of the present invention are glossy despite their thin film thickness of 0.8 μm. In addition, it can be seen that the Vickers hardness of the platinum electrolytic precipitates of the embodiments 14 to 16 of the present invention is 465 to 480 Hv, which is relatively hard, and the porosity is also in the range of 10.2 to 13.8%, which is excellent in corrosion resistance. Moreover, the purity of platinum is 99%. In addition, it can be seen that the internal stress of the embodiments 14 to 16 of the present invention is in the range of 20 to 80 MPa, which is extremely low. In contrast, it can be seen that the porosity of the platinum electrolytic plating bath of the comparative product 01 is 30.6%, the platinum electrolytic plating bath of the comparative product 02 is 35.1%, and the platinum electrolytic plating bath of the comparative product 03 is also 33.5%, which are all extremely high. It can also be seen that the internal stress of the platinum electrolytic precipitates of the comparative products 01 to 03 is also 450 to 550 MPa, which is extremely high. Although the porosity of Comparative Products 01 to 03 was poor, no cracks or pinholes were found in appearance.
[0141] On the other hand, a Hall cell test was performed on the platinum electrolytic plating bath of Comparative Example 3 and the platinum electrolytic plating bath of Example 1. The platinum electrolytic plating bath of Example 1 contained 60 mg / L of sodium lauryl sulfate, and the platinum electrolytic plating bath of Comparative Example 3 contained 600 mg / L of sodium lauryl sulfate. Visual observation of the amorphous plated area of the Hall cell sample revealed that the platinum electrolytic plating bath of Comparative Example 3 was inferior to the platinum electrolytic plating bath of Example 1 by about 50% on the high current density side.
[0142] As described above, it can be seen that the platinum electrolytic plating bath of the present invention can obtain a high-purity platinum film, but has low porosity and excellent corrosion resistance. In addition, the platinum-plated product of the present invention is dense, has low stress, and is shiny, so it can be used not only in electrical parts such as connectors and printed circuit boards, but also in seawater electrolysis electrodes, insoluble anodes for electroplating, jewelry, and many other uses.
Claims
1. An acidic platinum electrolytic plating bath having a pH value of ≤2 and capable of obtaining a platinum precipitate having a purity of 99 wt % or more, characterized in that: An acidic platinum plating bath comprising a divalent platinum (II) complex and 30-600 g / L of free sulfuric acid or sulfamic acid contains 5-500 mg / L of anionic surfactant, wherein the content of platinum in the divalent platinum (II) complex is 1-20 g / L, wherein the anionic surfactant is selected from one or a combination of two or more of the following groups: Alkyl sulfuric acid or its salt, alkylbenzene sulfonic acid or its salt, stearic acid or its salt and sulfonic acid or its salt.
2. An acidic platinum electrolytic plating bath having a pH value of ≤ 2 and capable of obtaining a platinum precipitate having a purity of 99 wt % or more, characterized in that: In an acidic platinum plating bath comprising a divalent platinum (II) complex and 30-600 g / L of free sulfuric acid or aminosulfonic acid, 5-500 mg / L of anionic surfactant and a metal salt of a second main group element or a metal salt of an alkali metal element are contained, wherein the content of platinum in the divalent platinum (II) complex is 1-20 g / L, wherein the anionic surfactant is selected from one or a combination of two or more of the following groups: Alkyl sulfuric acid or its salt, alkylbenzene sulfonic acid or its salt, stearic acid or its salt and sulfonic acid or its salt.
3. An acidic platinum electrolytic plating bath having a pH value of ≤ 2 and capable of obtaining a platinum precipitate having a purity of 99 wt % or more, characterized in that: An acidic platinum plating bath comprising a divalent platinum (II) complex and 30-600 g / L of free sulfuric acid or aminosulfonic acid contains 5-500 mg / L of anionic surfactant; the content of platinum in the divalent platinum (II) complex is 1-20 g / L; The anionic surfactant is selected from one or a combination of two or more of the following groups: Alkyl sulfuric acid or its salt, alkylbenzenesulfonic acid or its salt, stearic acid or its salt, sulfonic acid or its salt, alkali metal salt of lauryl sulfate, salt of the second main group element, ammonium salt.
4. An acidic platinum electrolytic plating bath having a pH value of ≤ 2 and capable of obtaining a platinum precipitate having a purity of 99 wt % or more, characterized in that: An acidic platinum plating bath comprising a divalent platinum (II) complex and 30-600 g / L of free sulfuric acid or aminosulfonic acid, wherein the bath contains 5-500 mg / L of anionic surfactant and a metal salt of a second main group element or a metal salt of an alkali metal element; the content of platinum in the divalent platinum (II) complex is 1-20 g / L; The anionic surfactant is selected from one or a combination of two or more of the following groups: Alkyl sulfuric acid or its salt, alkylbenzenesulfonic acid or its salt, stearic acid or its salt, sulfonic acid or its salt, or alkali metal salt, second main group element salt, ammonium salt of lauryl sulfate.
5. An acidic platinum electrolytic plating bath having a pH value of ≤ 2 and capable of obtaining a platinum precipitate having a purity of 99 wt % or more, characterized in that: An acidic platinum plating bath comprising a divalent platinum (II) complex and 30-600 g / L of free sulfuric acid or aminosulfonic acid, wherein the bath contains 5-500 mg / L of anionic surfactant; the content of platinum in the divalent platinum (II) complex is 1-20 g / L; The anionic surfactant is one of sodium lauryl sulfate, sodium N-lauroyl sarcosinate, a combination of alkyl allyl sulfonate and alkyl ammonium salt, ammonium lauryl sulfate, sodium stearate, sodium alkyl benzene sulfonate, potassium lauryl sulfate, sodium 1-octadecyl sulfonate, and dimethyl 5-sulfophthalate.
6. The acidic platinum electrolytic plating bath having a pH value of ≤ 2 and capable of obtaining a platinum precipitate having a purity of 99 wt % or more according to claim 5, characterized in that: The sodium alkylbenzene sulfonate includes sodium dodecylbenzene sulfonate.
7. An acidic platinum electrolytic plating bath having a pH value of ≤ 2 and capable of obtaining a platinum precipitate having a purity of 99 wt % or more, characterized in that: An acidic platinum plating bath comprising a divalent platinum (II) complex and 30-600 g / L of free sulfuric acid or aminosulfonic acid, wherein the bath contains a metal salt of a second main group element and 5-500 mg / L of an anionic surfactant; the content of platinum in the divalent platinum (II) complex is 1-20 g / L; The anionic surfactant is one of sodium lauryl sulfate, sodium N-lauroyl sarcosinate, a combination of alkyl allyl sulfonate and alkyl ammonium salt, ammonium lauryl sulfate, sodium stearate, sodium alkyl benzene sulfonate, potassium lauryl sulfate, sodium 1-octadecyl sulfonate, and dimethyl 5-sulfophthalate.
8. The acidic platinum electrolytic plating bath having a pH value of ≤ 2 and capable of obtaining a platinum precipitate having a purity of 99 wt % or more according to claim 7, characterized in that: The sodium alkylbenzene sulfonate includes sodium dodecylbenzene sulfonate.
9. The platinum electrolytic plating bath according to any one of claims 1 to 8, characterized in that: The divalent platinum (II) complex has at least one ligand selected from the group consisting of a nitro group, a nitrate group, a sulfate group or a sulfonate group, and an amino group, an oxonium group or a hydroxyl group.
10. A platinum-plated product, characterized in that: A platinum-plated product comprising a platinum electrolytic precipitate obtained using a platinum electrolytic plating bath according to any one of claims 1 to 8, wherein the platinum purity in the film formed by the electrolytic precipitate is greater than or equal to 99% by weight, the Vickers hardness is 450 to 500 Hv, the stress is less than or equal to 100 MPa, and the porosity is less than or equal to 30%.
11. The platinum-plated product according to claim 10, characterized in that: The silicon content of the platinum-plated product is less than or equal to 1 ppm, and the remainder is platinum electrolytic precipitate.
